Atina Demokrasisinden Roma Cumhuriyetine - "Demos"tan "Populus Romanus"a - (:unkn) unknown (My University, 2017)
Modern devletin kurumsal ve ideolojik kökenleri Atina Demokrasisinde ve Roma Cumhuriyetinde bulunmaktadır. Antik Yunan'da demokrasi, her yurttaş tarafından kanun yapım sürecine katılmak için eşit ve anlamlı bir şansa sahip olmayı ifade ediyordu. Atina'da yurttaşlar "demos"u, "res publica"da ise "populus romanus"u oluşturmaktadır. Antik Yunanın ünlü filozofları Platon ve Aristoteles, demokrasiyi kötü yönetim olarak eleştirmektedirler. Atina'da yurttaşların tümü yasaların yapılmasına ve uygulanmasına katılmaktadır. Atina demokrasisinde, isegoria ve isonomia iki önemli eşitlik ilkesidir. Roma'da Cumhuriyet patrici-plep çatışması sonucu kurulmuş ve gelişmiştir. Roma Cumhuriyeti bir karma yönetim modelidir ve Populus "potestas"a, Senato ise "auctoritas"a sahiptir. Günümüzde demokrasilerin bir ilkesi olan kuvvetler ayrılığının kaynağı karma yönetimdir.

The institutional and ideological roots of the modern state are found in the Democracy of Athens and the Roman Republic. In ancient Greece, democracy means having an equal and meaningful chance to take part in lawmaking process by each and every citizen. Citizens constitute "demos" in Athens and "populus romanus" in "res publica". Plato and Aristotle, famous philosophers of ancient Greece, criticize democracy as a bad governance. In Athens, all citizens are involved in the implementation and enforcement of law. In the democracy of Athens, isegoria and isonomia are two important principles of equality. The Republic was established and developed as a result of the patriciplep conflict in Rome. The Roman Republic is a mixed governance model and the Populus has the "potestas", while the Senate has the "auctoritas". In modern world, the source of the separation of forces which is a principle of the democracy, is mixed government.
From Democracy Of Athens To The Republic Of Rome- From "Demos" To "Populus Romanus"
Keywords: Arkeoloji